STUDI KEPATUHAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR DENGAN PEMUTIHAN PAJAK SEBAGAI VARIABEL MODERASI - Diaz Juan Marcheita,; Arif Nugroho Rachman, (Juremi: Jurnal Riset Ekonomi, 2022)
The purpose of this research is to determine the effect of taxpayer awareness, sanctions, and income level on taxpayer compliance in paying motor vehicle taxes and to determine the moderation of perceptions of tax bleaching program on the effect of taxpayer awareness, sanctions, and income level on compliance taxpayer in paying motor vehicle tax. The population in this study are all two-wheeled motorized vehicle taxpayers in Surakarta. Sampling using purposive sampling technique with the criteria of taxpayers who joined in the tax bleaching program. The samples tested are 100 samples using multiple linear regression analysis technique to test the effect of awareness, sanctions and income level on tax compliance in paying motor vehicle taxes and moderate regression analysis (MRA) to test the moderating effect of tax bleaching perceptions on the effect of taxpayer awareness, sanctions and income level on taxpayer compliance in paying motor vehicle tax. The result of this research state that taxpayer awareness, sanctions, and income level have a positive effect on taxpayer compliance in paying motor vehicle taxes. However, the perception of tax bleaching cannot moderate the effect of taxpayer awareness, sanctions, and income level on taxpayer compliance in paying motor vehicle tax in Surakarta.